Distinct Mechanisms in Number Comparison of Random and Regular Dots: An ERP Study - Liu, Wei; Zhao, Yajun; Wang, Chunhui; Wang, Lu; Fu, Ying; Zhang, Zhijun (Frontiers in Behavioral Neuroscience, 2022)
Numerosity comparison for regular patterns shows different features compared with that for random ones in previous studies, suggesting an underlying mechanism distinct from numerosity. In the current study, we went further to compare the ERP components in numerosity processing of random and regular patterns, which are identical in all aspects of texture features except for the distribution. ERP components were recorded and analyzed while participants compared which of the two successively presented sets was more numerous. P2p amplitude was revealed to be significantly weaker for regular patterns compared with that for random patterns over right occipital-parietal cites, whereas no difference was found for P1 or N1 components. Difference in P2p amplitude, which is consistent with the behaviour dissociation revealed in our previous studies, suggests that regular distribution can trigger distinct processing in numeral comparison tasks. Processing of continuous magnitudes or configuration cannot explain the decrease in P2p amplitude for regular distributed patterns. Hence this study further supports that P2p is mediated by numerosity processing.